Chagasic thymic atrophy does not affect negative selection but results in the export of activated CD4+CD8+ T cells in severe forms of human disease - Morrot, Alexandre (2011)
Universidade Federal do Rio de Janeiro. Instituto de Microbiologia. Departamento de Imunologia. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisa sobre o Timo. Rio de Janeiro, RJ, Brasil.